The Influence of Location and Price Perception on Visiting Decisions Tour The Hot Springs of Citiis Galunggung in Tasikmalaya Regency - Neng Gita Jannatun Nisa; Budhi Wahyu Fitriadi; Depy Muhamad Pauzy (Journal of Indonesian Management, 2022)
This study aims to determine the effect of location and price perception on visiting decisions tour the hot springs of Citiis Galunggung in Tasikmalaya Regency. The method used is a quantitative approach with the survey method. With a research sample of 100 visitors Citiis Galunggung hot spring tour in Tasikmalaya regency. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 25.0. The results showed that the location by visitors of Citiis Galunggung. Location had good criteria. The price perception of Citiis Galunggung had good criteria. Visiting decisions on visitors of Citiis Galunggung have good criteria. Simultaneously location and price perception have a significant influence on purchasing visit. Partially location has a significant influence on purchasing visit.. Partially price perception has a significant effect on purchasing visit.